Effects of delayed first feeding on some enzymes and on the development of the digestive tract and skeletal muscles of Nile tilapia, Oreochromis niloticus L. - Fabillo, Melodina D. 1976 (2004)
To compare the effects of stravation before initial feeding on the digestive enzymes and development of the digestive tract and skeletal muscles of the genetically male tilapia (product of a cross between the supermale YY father and ordinary XX female), fish were for 2,4,6 and 8 days before first feeding...
"March 2004."
Vita.
Thesis (M.S. Biology)--University of the Philippines Diliman.
Keywords: Nile tilapia -- Philippines -- Growth; Nile